Allelic Variants Within the ABO Blood Group Phenotype Confer Protection Against Critical COVID-19 Hospital Presentation - Jelinek, Herbert F.; Mousa, Mira; Alkaabi, Nawal; Alefishat, Eman; Daw Elbait, Gihan; Kannout, Hussein; AlHumaidan, Hiba; Selvaraj, Francis Amirtharaj; Imambaccus, Hala; Weber, Stefan; Uddin, Maimunah; Abdulkarim, Fatema; et al. (Frontiers in Medicine, 2022)
Introduction COVID-19 disease severity differs widely due to numerous factors, including ABO gene-derived susceptibility or resistance. The objective of this study was to investigate the association of ABO blood group and genetic variations of the ABO gene with COVID-19 severity in a heterogeneous hospital population sample from the United Arab Emirates, with the use of an epidemiological and candidate gene approach from a genome wide association study (GWAS). Method In this cross-sectional study, a total of 646 participants who tested positive for SARS-CoV-2 were recruited from multiple hospitals and population-based (quarantine camps) recruitment sites from March 2020 to February 2021. The participants were divided into two groups based on the severity of COVID-19, non-critical (n=453) or critical (ICU patients) (n=193), as per the COVID-19 CO-RADS classification. A multivariate logistic regression analysis demonstrated the association of ABO blood type, as well as circulating anti-A antibodies and anti-B antibodies, as well as A and B antigens, in association with critical COVID-19 hospital presentation. A candidate gene analysis approach was conducted from a GWAS where we examined 240 SNPs (Position in chr9: 136125788-136150617) in the ABO gene, in association with critical COVID-19 hospital presentation. Results Patients with blood group O (OR: 0.51 (0.33, 0.79); p-value=0.003) were less likely to develop critical COVID-19 symptoms. Eight alleles have been identified to be associated with a protective effect of blood group O in ABO 3’untranslated region (UTR): rs199969472 (p-value=0.0052), rs34266669 (p-value=0.0052), rs76700116 (p-value=0.0052), rs7849280 (p-value=0.0052), rs34039247 (p-value=0.0104), rs10901251 (p-value=0.0165), rs9411475 (p-value=0.0377), and rs13291798 (p-value=0.0377). Conclusion Our findings suggest that there are novel allelic variants that link genetic variants of the ABO gene and ABO blood groups contributing to the reduced risk of critical COVID-19 disease. The current study is the first to combine genetic and serological evidence of the involvement of the ABO blood groups and ABO gene allelic associations with COVID-19 severity within a Middle Eastern population